Union of Comoros : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Union of Comoros. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights difficulties the economy of Comoros encountered in 2015 and the first half of 2016. An ongoing crisis in the electricity sector and slower-than-expected implementation of the public investment program were the main factors behind the slower growth. Inflation remained well anchored at an annual rate of about 2 percent. Fiscal policy was challenging for most of 2015 as the impact of slower economic growth was compounded by lower revenues. Growth is projected to pick up somewhat to 2 percent in 2016, and revenues are projected to increase to 12 percent of GDP.